The CSR-Quality Trade-Off: When can Corporate Social Responsibility and Corporate Ability Compensate Each Other? - Berens, Guido (Journal of business ethics, 2007)
This paper investigates under what conditions a good corporate social responsibility (CSR) can compensate for a relatively poor corporate ability (CA) (quality), and vice versa. The authors conducted an experiment among business administration students, in which information about a financial services company’s CA and CSR was provided. Participants indicated their preferences for the company’s products, stocks, and jobs. The results show that for stock and job preferences, a poor CA can be compensated by a good CSR. For product preferences, a poor CA could not be compensated by a good CSR, at least when people thought that CA is personally relevant to them. Furthermore, a poor CSR could be compensated by a good CA for product, stocks, and job preferences.